2022
DOI: 10.1007/s12602-022-09963-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiotic Potential of Gamma-Aminobutyric Acid–Producing Marine Enterococcus faecium SH9 from Marine Shrimp

Abstract: Psychobiotics are a novel class of probiotics with potential to confer mental wellness via production of neuroactive compounds such as gamma-aminobutyric acid (GABA). The demand for new biological sources of GABA has increased steadily. Therefore, the current study reports the isolation of 17 presumptive lactic acid bacteria (LAB) from marine samples and their screening for GABA synthesis from monosodium glutamate (MSG) using thin-layer chromatography (TLC). The isolate SH9 was selected as a high GABA producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…There was a 21% increase in viability compared to the initial concentration. Similar results for E. faecium were observed at different phenol concentrations (0.25%, 0.40%, and 0.50%) for 18-24 h at 30-37°C (Sakkaa et al, 2022;Siddique et al, 2021;Tilwani et al, 2022;Vadassery & Pillai, 2020).…”
Section: Re Sult and Discussionsupporting
confidence: 83%
“…There was a 21% increase in viability compared to the initial concentration. Similar results for E. faecium were observed at different phenol concentrations (0.25%, 0.40%, and 0.50%) for 18-24 h at 30-37°C (Sakkaa et al, 2022;Siddique et al, 2021;Tilwani et al, 2022;Vadassery & Pillai, 2020).…”
Section: Re Sult and Discussionsupporting
confidence: 83%
“…The control for this test was a mixture of 1.5 mL DPPH and 1.5 mL methanol. Antioxidant activity, expressed as scavenging activity percentage, was calculated using the following formula ( Archer and Halami, 2015 ; Sakkaa et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…A particular GABA-producing enterococcal strain, isolated from the gut of marine shrimp, was tested in vitro for the production of GABA. Thin Layer Chromatography (TLC) analysis showed that the Enterococcus isolates exhibited high GABA production, suggesting its potential role in neurological modulation [ 41 ].…”
Section: Probiotic Potential (Efficacy Of Enterococcal Strains)mentioning
confidence: 99%